2010
DOI: 10.1245/s10434-010-1186-x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Soft Part Sarcoma: Clinical Presentation, Treatment, and Outcome in a Series of 33 Patients at a Single Institution

Abstract: Prognosis of ASPS is basically related to the characteristics of the disease and the quality of surgery. Overall, the occurrence of distant metastases is quite common, with a typical indolent course. New agents are eagerly needed to complement surgery to eradicate this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
69
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 18 publications
3
69
1
Order By: Relevance
“…The most common sites of ASPS are the deep muscles of the lower limbs. ASPSs also occur in other parts, such as the head and neck, the mediastinum, and the retroperitoneum [8]. It grows slowly, shows strong enhancement and has a slow painless progress and a tendency to metastasize [9].…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites of ASPS are the deep muscles of the lower limbs. ASPSs also occur in other parts, such as the head and neck, the mediastinum, and the retroperitoneum [8]. It grows slowly, shows strong enhancement and has a slow painless progress and a tendency to metastasize [9].…”
Section: Discussionmentioning
confidence: 99%
“…The status of the surgical margins is also a significant prognostic factor. Patients who underwent complete resection showed better prognoses than those who underwent incomplete or marginal resection [24].…”
Section: Discussionmentioning
confidence: 88%
“…Tumor size has been shown to be a prognostic factor. Several reports have indicated that patients with tumors less than 5 cm in diameter had significantly better prognoses than those with larger tumors [20][21][22][23][24]. The status of the surgical margins is also a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of imatinib for gastrointestinal stromaltumors(GIST) [2]canserveasanexample.Alveolar softpartsarcoma(ASPS)isanextremelyraresubtypeofsoft tissue sarcoma. It is characterized by translocation der(17) t(X:17)(p11;p25)ononehand,andausuallyindolentgrowth patternontheother [3].SimilartoGIST,itisquiteinsensitive tothecommonlyusedcytotoxicdrugs [4].…”
mentioning
confidence: 99%